Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1007/bf00500374
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose levels in diabetic and non-diabetic subjects

Abstract: Most, if not all, diabetologists are convinced, on the basis of indirect evidence which has been accumulated over the decades that the microangiopathic and neurological complications of diabetes are primarily dependent on the duration and extent of chronic hyperglycaemia [1-5]. Hyperglycaemia is the necessary factor in the development of these complications even if other, secondary factors, sometimes responsive to treatment, such as blood pressure levels, smoking, protein intake, with or without genetic predis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Many authors reported that, in fasting conditions, there is a smaller resting glucose concentration in women compared to men (Hautecouverture et al 1974;Selmi et al 1976;Tchobroutsky 1991). In the present study, the carbohydrate ingestion during breakfast was the same in both sexes, since all subjects ate a standardized breakfast.…”
Section: Discussionmentioning
confidence: 94%
“…Many authors reported that, in fasting conditions, there is a smaller resting glucose concentration in women compared to men (Hautecouverture et al 1974;Selmi et al 1976;Tchobroutsky 1991). In the present study, the carbohydrate ingestion during breakfast was the same in both sexes, since all subjects ate a standardized breakfast.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical profiles of the subjects with GCK mutations and their controls are shown in Table I. Mean fasting glucose levels were significantly higher in the subjects with GCK mutations (6.72±0.12 vs. 5.04±0.17 mM, P < 0.0008), and they all had fasting glucose values > 6.1 mM which is 2 SD greater than the mean value in a matched nondiabetic French population (7). Glycosylated hemoglobin values (Glyc-Affin GHb kit, Isolab, Inc., Akron, OH) were available in four of the six subjects with mutations (GK3, GK4, GK5, and GK6) and all were above 6.2% which is the upper limit of normal in …”
Section: Subjectsmentioning
confidence: 94%
“…Reference intervals are not useful for diagnosing these conditions. In adults, the mean FPG concentration increases with increasing age from the third to the sixth decade (71) but does not increase significantly after 60 years of age (72,73). By contrast, glucose concentrations after a glucose challenge are substantially higher in older individuals (72,73).…”
Section: Glucosementioning
confidence: 99%